1992
DOI: 10.1177/000456329202900506
|View full text |Cite
|
Sign up to set email alerts
|

Reference Values of Serum and Urine Creatinine, and of Creatinine Clearance by a New Enzymatic Method

Abstract: SUMMARY. A new, totally enzymatic procedure for the determination of creatinine in serum and urine, using creatinine amidohydrolase, creatine amidinohydrolase, sarcosine oxidase and formaldehyde dehydrogenase is described. The assay was adapted to a discontinuous analyser with each analysis requiring only 20 J.lL of serum or 3 J.lL of urine. Analytical recovery of creatinine in serum and urine averaged 100· 61170. Within-run and between-run precision studies gave coefficients of variation of 1·1 % and I· 8%, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Colorimetric determinations of the picrate salt or assays based on enzymatic reactions are commonly used in clinical chemistry [11,12,13]. Creatinine assays examining the reaction of creatinine and picric acid were first reported by Jaffé [14].…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric determinations of the picrate salt or assays based on enzymatic reactions are commonly used in clinical chemistry [11,12,13]. Creatinine assays examining the reaction of creatinine and picric acid were first reported by Jaffé [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore precision is needed in order to detect a true change in function from a variability in the measurement tech nique. Previous studies using total chromogen, such as that determined by an autoanalyser, as a measure of serum and urine creatinine have suggested that creatinine clearance has a low precision [2], However, this is likely to be accounted for by the variable contribution of noncrea tinine chromogens to the creatinine assay [11,23], which in general, is relatively less of a problem at higher levels of plasma creatinine. In a study comparing the effect of interfering substances on the measurement of creatinine, 28 different laboratories routinely using 17 different methods for the determination of serum creatinine (three major variations of the alkaline picrate method and two 280 Pollock/Gyory/Hawkins/Ross/Ibcls True Creatinine versus Iothalamate Clearances enzymatic methods), assayed samples containing plasma alone, or with the addition of 55 mmol/1 glucose, or 10 mmol/1 acetoacetate or 320 pl/1 or 2 mmol/1 cefotoxin [24].…”
Section: Discussionmentioning
confidence: 99%
“…The 24 h urine creatinine correlation with total lean body mass (LBM) has been verified [16] and the decrease in LBM association with aging results from a specific loss of muscle [17]. A 24 h urine creatinine difference between genders has been observed; men show higher values than women and it decreases with age in both genders [10,18,19]. The aim of our work was to carry out a simple, rapid, and cheap CE method to measure creatinine in extemporaneous diluted urine.…”
Section: Introductionmentioning
confidence: 86%
“…The JaffØ reaction is a method in which a creatininepicrate adduct is formed, but this assay is not completely specific because several of the urine substances form colored molecules with alkaline picrate reagent [1,2]. Other methods use chromatographic separation [3±6], ionselective electrode as well as oxygen-sensitive electrodes [7±9], and also enzymatic methods [10,11]. Some of these methods present interferences and others are expensive.…”
Section: Introductionmentioning
confidence: 99%